A glimpse of indigenous and minor vegetables of India - Ram, Hari Har; Kushwaha, Sunita; Dubey, Rakesh Kumar (Indian Horticulture, 2020)
Indigenous (traditional) vegetables are best defined as species that are locally important for the sustainability of economies, human nutrition and health, and social systems but which have yet to attain global recognition to the same extent as major vegetable commodities such as tomato or cabbage. Indigenous vegetables - plant species consumed in specific locations as part of traditional diets - have the potential to diversify cropping systems, increase farm income, and add a range of vital micronutrients to diets. Given the hundreds of indigenous vegetables consumed worldwide, their accumulated value for mankind is considerable. These species deserve much greater recognition and investment in agricultural research and development than they have received presently.